DIY Tapestri Kit As An Alternative Art Activity In The Pandemic Era - Cynthia Zhafira Aulia Imas (Corak, 2022)
The spread of the corona virus forced some people to school or work from home that might end in boredom. Art activities could be done to fill their leisure time and at the same time to entertain them selves. One of the artistic activities needed to be developed was the art of tapestry. The Practice Based Research method was a method employed in designing a DIY Tapestri Kit. The main goal was to inspire and increase the public’s awareness about the existence of tapestry art. DIY Tapestry Kit was a set of tapestry art handicraft tools in the form of looms with a variety of yarns that could be used to produce a variety of functional artworks. The existence of innovations in the form of DIY Tapestry Kit supported the on-going and subsequent implementation of tapestry art.